Application of a novel three-day repetitive transcranial magnetic stimulation protocol for the treatment of drug-resistant epilepsy in dogs: single-blinded randomised sham-controlled clinical trial - Charalambous, Marios; Hünting, Delia; Meyerhoff, Nina; Twele, Friederike; Meller, Sebastian; Volk, Holger A. (Frontiers in Veterinary Science, 2025)
While the efficacy of repetitive transcranial magnetic stimulation (rTMS) has been explored in humans and, to a lesser extent, in dogs with epilepsy, further clinical studies are required to assess the potential antiseizure effect of this non-invasive neurostimulation technique. The objective was to assess the antiseizure effect and safety of a novel three-day rTMS protocol in dogs with drug-resistant idiopathic epilepsy. A single-blinded, randomized, sham-controlled clinical trial was conducted by randomly allocating 20 dogs with drug-resistant idiopathic epilepsy or epilepsy of unknown origin into active (n = 10) or sham (n = 10) rTMS. The monthly seizure frequency (MSF), monthly seizure day frequency (MSDF), and number of cluster seizures (CS) were recorded and comparisons between the two groups were analysed. The safety of the rTMS protocol was also evaluated. Statistically significant differences were identified between the groups in median MSF (active, 8 [0–24]; sham, 17 [7–46]; p = 0.04), MSDF (active, 8 [0–24]; sham, 11 [6–23]; p = 0.04), and number of CS (active, 10 [5–23]; sham, 16 [10–25]; p = 0.005). No adverse events were reported. The current protocol indicates that active rTMS is safe, can reduce seizure frequency, and prevent CS in dogs with drug-resistant idiopathic epilepsy or epilepsy of unknown origin. An “one-size-fits-all” rTMS protocol for epilepsy in dogs is likely to provide suboptimal outcomes because the effect of rTMS is highly dependent on the duration and parameters of stimulation as well as individual variability. Therefore, future studies are needed to explore further specific stimulation parameters so they can be better tailored to the individual dog.